The man in the iron mask - Dumas, Alexandre (Penguin, 2003)
In this classic swashbuckling tale-- one of the great adventures of all time-- Alexandre Dumas's Three Mukateers are pitted against one another in a terrifying fight for the throne of France. The adventure begins deep inside the Bastille, where a twenty-three-year-old prisoner named "Philippe" has languished for eight long years, unaware of his true identity or what crime he has committed. When Aramis, one of the original Three Muskateers, bribes his way into his cell, the shocking secret that has kept Philippe locked away from the world is revealed--a secret that could destroy King Louis XIV. What follows may divide Athos, Pothos, and D'Artagnan forever and cause Aramis to betray his sacred vow of "All for one, and one for all!". With its daring jailbreak, brilliant masquerade, and heart-stopping sword play, The Man in the Iron Mask contains all the pomp, pageantry, and colorful history that make the novels of Alexandre Dumas so wonderful to read. It is an incomparable tale of honor and loyalty, adventure and derring-do.